Penguatan Manajemen Modal Kerja Sebagai Kelangsungan Start-Up Kawasan UNNES - Ita Nuryana, Margunani, Suwito Eko Pramono (Universitas PGRI Madiun, 2019)
Lack of knowledge about working capital management caused the sustainability of start-ups in UNNES area is still being low. It resulted that manager of start-ups are difficult to develop themselves. Therefore, it need for training to improve the skills in making good financial, so the sustainability of start-ups is reached. To increase of the existence and sustainability of start-ups are also required the reinforcement of working capital management by manager of the start-up. Then, focus of devotion is the owner and manager of the start-ups in UNNES area that gathered in HIPMI PT UNNES. Purpose of this devotion is improving and making good working capital management for the sustainability of start-up. Participants in this devotion 25 people. Procedure in this devotion is carried out by delivering of material on working capital management. In supporting of devotion, the dedication team arranges the module of working capital management. Outcome of this devotion is creating that the manger of the start-up can continue their start-up, so it can reduce the number of unemployment.